Fowler's Modern English Usage - Fowler H. W.; Burchfield R. W. (New Delhi, Oxford University Press, 2006)
Comprehensive, practical advice on grammar, syntax, style, and choice of words. Controversial or disputed usage explained in full, with clear unequivocal guidance. Based on the unrivalled language resources of Oxford Dictionaries, the largest langauge research programme in the world In-depth coverage of both British and American English, with reference to the English of Australia, Canada, New Zealand, and South Africa Wide-ranging examples of actual usage, taken from a broad selection of newspapers, journals, and books from across the globe'To consult Fowler is to consult the oracle. Those of us who get worked up about English can turn to Fowler: he smoothes one's fevered brow.